A Rare Presentation of Osteoid Osteoma in a 77-Year-Old Patient, Treated with Computer Tomography–Guided Percutaneous Radiofrequency Ablation - Patel, Anish; Davies, Mark; James, Steven; Azzopardi, Christine; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2021)
Osteoid osteoma (OO) is a benign bone forming tumor characterized by small size and a disproportionate amount of pain. They are most commonly seen between the ages of 5 and 30 years; however, they can be seen in the older patient albeit infrequently. The hands and feet are the least common site of OO among the extremity bones. We present a case of an OO in the hand of a 77-year-old man who underwent successful treatment with computed tomography–guided percutaneous radiofrequency ablation. We believe this is the oldest recorded patient in the medical literature with a histologically confirmed OO. The condition should therefore be considered in the differential diagnosis of a painful sclerotic bone lesion in this age group to avoid a delay in diagnosis and subsequent treatment.
Keywords: bone tumor; osteoblastic tumor; osteoid osteoma; radiofrequency ablation